EVALUASI METODOLOGI DESAIN DALAM SIMULASI PERANCANGAN ULANG SISTEM TANDA UNTUK PENGGUNA TRANSPORTASI UMUM - Brian Alvin Hananto; Jessie Rose Komala Hadi; Karina Olivia Hernawan; Natasha Christina Gondo (LPPM Institut Bisnis dan Teknologi Indonesia, 2020)
A design methodology is an important aspect of design. In hopes to develop the design methodology’s pedagogy in the Visual Communication Design Department of Universitas Pelita Harapan (VCD UPH), the author conducted a classroom action research to evaluate results of design methodology analysis of final assignment projects in VCD UPH. The project that is featured in this article is a signage system redesign for Transjakarta by Triska, in which several students in the Design Methodology class evaluate the methodology. For the evaluation, Triska’s methodology is framed by the design process model of Robin Landa. The result of the evaluation shows several points that can be added from Triska’s methodology to make it better. From the study, it is shown that design methodology learning can be conducted through analysis and evaluation of a design methodology of a design project. The learning method is possible to be implemented for the bachelor level of design programs. Though the pedagogy demonstrated in this article is still in its preliminary phase, it can later be further developed after more studies and the second cycle of research had been done by the author.